Combination of Tung oil and Natural Rubber Latex in PVA as Water Based Coatings for Paperboard Application - Apichaya Jianprasert; Pathavuth Monvisade; Masayuki Yamaguchi (My University, 2015)
This research is focused on the preparation of the PVA/TO/NRL coatings for paperboard by using poly(vinyl alcohol) (PVA) as substance and blending with Tung oil (TO) and/or natural rubber latex (NRL) in order to enhance water resistance and dynamic mechanical properties. The effects of TO: NRL ratios on the structures were investigated by water resistance property and dynamic mechanical thermal analysis (DMA). The results showed that the water resistance property was improved by crosslinking of TO and film forming of NRL. The PVA/TO/NRL coating containing both TO and NRL gave better thermal behavior than those with only TO or NRL. For paperboard application, the PVA/TO/NRL coatings were applied on the paperboard to study water affinity and absorption rate on the coated surface. The rate of contact angle change of water on coated paperboards decreased depending on the ratios of TO and NRL.
Keywords: Paperboard; Vinyl alcohol; Material Properties and Processing